Control Behaviors of Fathers and Pregnant Women on Adherence of Pregnant Women to Take Blood Supplement Tablets - Galuh Pradian Yanuaringsih; Putri Wahyu Wigati; Sutrisni Sutrisni (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Anemia prevention programs in pregnant women often involve the consumption of blood supplement tablets in pregnant women, and an understanding of the role of fathers and pregnant women in supporting adherence is essential to improve the effectiveness of such programs. In certain populations, such as pregnant women, anemia can have a serious impact on health and development. In pregnant women, anemia can increase the risk of premature birth, low birth weight, and maternal death. The aim of the study was to determine which factors of paternal and maternal control behaviors were correlated with maternal adherence to blood supplementation tablets.This research was conducted quantitatively with a cross-sectional approach. The sample included 214 married couples in Kediri City which was taken using random sampling technique in March 2024. Data were collected using a questionnaire that included questions on paternal and maternal control behaviors, compliance with blood supplementation tablet consumption. Univariate and bivariate were the two stages of data analysis, chi-square test was used for bivariate analysis.The results showed that paternal control behaviors (paternal knowledge, support) and maternal control behaviors (self-efficacy, attitudes, side effects) had values >0.05 which means there is no correlation with pregnant women's adherence to taking blood supplement tablets, while father's control variables (trust, father's attitude) and mother's control variables (media exposure, mother's knowledge) <0.05, which means there is a correlation with pregnant women's adherence to taking blood supplement tablets.his finding confirms that the role and control measures of fathers are critical to support pregnant women's adherence to taking blood tablets. Keyword: Adherence, Blood Supplementation Tablets, Control Behavior, Father, Pregnant Women